The Effectiveness of the Revitalization of Correctional Services in the Development of Terrorist Prisoners - Setya Wahyudi; Angkasa Angkasa; Dwi Hapsari Retnaningrum; Eriene Chindi Octaviandini (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Terrorist prisoners are characterized by the nature of radicalism that can endanger the existence of the Indonesian state. For this reason, while serving their prison sentences they are treated to a coaching program aimed at deradicalization. Concerning optimizing the development of prisoners, there are provisions of the Regulation of the Minister of Law and Human Rights Number 35 of 2018 concerning the Revitalization of Correctional Services. The revitalization of the implementation of the requirement is intended to improve the implementation of correctional duties and functions. This research is the first problem, how is the effectiveness of the revitalization of prisons in the development of terrorist prisoners, and the second is the factors that become obstacles in the effectiveness of the revitalization of coaching of terrorist prisoners. Research methods with a sociological juridical approach method, data in the form of primary data and secondary data taken from research locations at the Cipinang Jakarta Prison, Cirebon Prison, and Batu Malang Correctional Institution. Data analysis using qualitative analysis. The results of the study found that the revitalization of correctional services in the development of terrorist prisoners have not been effective because there has not been a complete creation of deradicalization. Obstacles to the effectiveness of the revitalization of coaching of terrorist prisoners are the legal structure factor and the legal cultural factor in terrorist prisoners. For ordinary prisoner coaches who are assigned the task of fostering terrorist prisoners (deradicalization), it is necessary to provide education and training on profiling and assessment of terrorist prisoners.Keywords:Deradicalization; Terrorist Prisoners; Revitalization